Creating a Japanese version of the attitudes toward dreams scale: Attitude toward dreams may predict sleep disorders. - Shinya Okuyama; Kenta Nozoe; Kazuhiko Fukuda; Takamasa Kogure; Shoichi Asaoka (PLoS ONE)
Previous studies have identified two factors that influence people's attitudes toward dreams: positive and negative. However, cultural differences may influence these attitudes. This study aimed to develop a Japanese version of a scale to assess attitudes toward dreams and to examine factors related to Japanese participants' attitudes toward dreams. These factors included dream attitudes, dream-recall frequency, and various sleep-related variables (Pittsburgh Sleep Quality Index, sleep apnea, restless legs syndrome, insomnia, and rapid eye movement sleep behavior disorder), personality traits, and quality of life. Additionally, we aimed to develop a new scale to measure dream attitudes. Nationwide data were collected from eight regions in Japan. We included 1,478 participants (728 men and 750 women) and assessed their dream attitudes, dream-recall frequency, several sleep variables, personality, and quality of life. We confirmed a two-factor structure similar to that previously described: Factor 1, named "meaning of dreams," reflects individuals' attitude to interpreting dreams, while Factor 2, named "no meaning of dreams," represents the attitude that dreams have no meaning. Both factors were significantly correlated with several variables. Factor 1 was more strongly correlated with rapid eye movement sleep-related variables. Scores for both factors declined with age, especially among individuals in their 60s and 70s. Factor 1 and dream-recall frequency showed significant sex differences among individuals in their 20s and 30s. Overall, we identified a two-factor structure of attitudes toward dreams, aligning with the Schredl scale. Factor 1 (meaning of dreams) was positively correlated with several dream- and rapid eye movement-related variables. Notably, a higher Factor 1 score in older individuals may indicate an increased risk of rapid eye movement sleep behavior disorder. The observed sex differences in dream-recall frequency may be based on differing attitudes toward dreams, particularly the tendency to find meaning in them, especially among younger individuals.